Hubungan Antara Pengetahuan Soft Drink dan Konsumsi SoftDrink dengan Kejadian Obesitas Pada Anak Usia Remaja di SMPBudi Mulia Dua Yogyakarta - Saputri, Rahmadya; , Susi Dyah Puspowati, SP., M.Si; , Pramudya Kurnia, STP, M.Agr (2013)
Introduction: : Health problems caused by nutritional problems divided poor nutritional status, poor nutrition, or nutrition / obesity. Obesity is a term used to indicate the presence of excess body fat normal limits. On the terms of a preliminary survey in SMP Budi Mulia Dua Yogyakarta in November 2011 that made the grade 1,2,3 total of 191 students found that the prevalence of obesity in adolescents is quite high, at 12.56%. Prevalence of soft drink consumption from the 65 students interviewed. The prevalence of students who consume soft drinks at 24.61%. Prevalence of obesity was higher when compared with adolescents in Yogyakarta research survey in 2004 which amounted to 7.8%. Soft drink intake is responsible for the excess energy that can lead to obesity. Objective: This study aimed to determine the relationship of knowledge of soft drink and consumption soft drink with the incidence of obesity in adolescents in SMP Budi Mulia Dua Yogyakarta. Research methods: Observational research with cross sectional approach. Sample obtained by sampling proportional sample of 79 respondents to the study inclusion and exclusion criteria samples. Knowledge of the data basis for taking soft drink using a food frequency questionnaire. statistical test used was chi-square test. Results: The results showed that most respondents have a good knowledge of soft drinks (55.7%). Most of the respondents have a soft drink consumption categories are often (62%). Statistical test results showed there is relationship between knowledge of soft drinks and soft drink consumption with obesity (p = 0.002 and p = 0.024). Conclusion: there is a relationship between knowledge of soft drinks and soft drink consumption with obesity